Reverse Flotation of Titanium Carbide from Garnet Mineral Using Cationic Surfactants - Khalek, M.A Abdel; Parekh, B.K (International Journal of Natural Sciences Research, 2013)
For cutting garnet rocks Titanium carbide (TiC) blades are used, which produces a fine waste material, a mixture of garnet and a few percent of Titanium carbide. In the present study, a reverse flotation technique was developed to recover the valuable Titanium carbide as tailings from the waste mixture using cationic surfactants such as, DA-1618 (Diethyl Amine ether) or DDAB (Dioctyl Dimethyl Ammonium Bromide) and poly-propylenimine (PPI) as a depressant for Titanium carbide. The effect of collector dosage, pH and depressant on the flotation parameters was investigated. It was found that both surfactants provided good recovery and grade of TiC, however DDAB was little better surfactant along with 0.35 kg/t of PPI at pH 9.0 provided 94% recovery of TiC with a grade of 97%.